Making community pharmacies psychologically informed environments: a pilot study to improve delivery of care for people with a drug problem. (1st April 2022) - Matheson, C; Hunter, C; Schofield, J; Parkes, T; Munro, A; O'Sullivan, K; Hunter, J
Abstract: Introduction: Community pharmacies are key in the delivery of care to people who use drugs (PWUD), providing specialist harm reduction, and treatment interventions such as naloxone, Injecting Equipment Provision and opiate replacement treatment. PWUD are disproportionately burdened with mental ill-health and frequently report trauma history which impacts on engagement. A successful approach in the homeless sector, is that of Psychologically Informed Environments (PIE). The core elements of a PIE are: creating a space which engenders a sense of safety and wellbeing; reflective practice so staff can develop a shared model of working; training and support for staff; and considering the therapeutic aspects of service provision to vulnerable people (1). Aim: This pilot study tested training pharmacy staff in applying a psychologically informed environments approach to improve the delivery of care to PWUD. Methods: Three pharmacies were recruited from those with high involvement with PWUD. A range of location and type of pharmacy were included. Whole pharmacy teams were invited to an evening training session. Bespoke training was provided by clinical psychologists with PIE expertise. Training was assessed by anonymous quantitative questionnaires using rating scales. Changes in the attitudes of staff were assessed by questionnaire before and 6 months after training. Descriptive statistics were applied. Qualitative interviews with staff at 6 months (planned for 3 months) explored what changes, were made after PIE training to adapt the delivery of care. The study used peer researcher-led telephone interviews for patient/client feedback on observed changes and experiences in participating pharmacies. Recruitment was via the three pharmacy teams due to covid restrictions. Thematic analysis was applied to qualitative data. Normalisation Process Theory provided a framework for assessing change. Results: Three pharmacies (16 staff) participated. Training evaluation was positive; all participants rating training structure and delivery as very good or excellent. Covid-19 lockdowns restricted follow-up data collection which took place at six months rather than three. Attitude scores were positive (>0) for all participants at baseline (median 15.0) increasing to 20.0 at 6 months. This was not statistically significant ( S =4, p =0.549). Staff interviews revealed training had encouraged staff to reflect on communication and considered the impact of current practice which could be discriminatory e.g. their use of first names, use of private areas and level of explanation to people. The increased mental health challenges for patients from Covid-19 restrictions gave an opportunity for staff to apply their new skills to this patient group and others who were struggling with isolation, as staff across pharmacies noted mental health challenges for patients. Five patients from two pharmacies were interviewed but time delays in data collection meant changes in delivery of care were difficult to recall. Conclusion: The study was limited by small sample size and covid-related delays. However, findings indicated that training whole pharmacy teams in PIE was well received and justifies a larger study. The approach allowed staff to reflect on practice and identify previous, potentially discriminatory practice. The importance of clear and compassionate communication was evident. Reference: (1) Johnson R, Haigh R. Social psychiatry and social policy for the 21st century ‐ new concepts for new needs: the 'psychologically‐informed environment.' Ment Heal Soc Incl. 2010;14(4):30–5.